Mental health and capacity laws in Northern Ireland and the COVID-19 pandemic: Examining powers, procedures and protections under emergency legislation. (July 2020) - Farrell, Anne-Maree; Hann, Patrick
Abstract: This article examines the changes made to mental health and capacity laws in Northern Ireland through temporary emergency legislation, known as the Coronavirus Act 2020. The purpose of the legislation was to respond to the emergency situation created by the COVID-19 pandemic, in particular the increase pressure placed on health services in the United Kingdom. An overview is provided of the government's rationale for the changes to Northern Ireland mental health and capacity laws, as well as exploring how they are likely to be operationalised in practice. Consideration is also given as to how such changes may impact upon existing human rights protections for persons assessed as lacking mental capacity. It is argued that it is important that regular parliamentary oversight is maintained in relation to the potential impact and consequences of such changes during the period they are in force. This should be done in order to assess whether they remain a necessary, proportionate and least restrictive response to the challenges faced in managing mental health and capacity issues in Northern Ireland during this public health emergency.